The High Time Resolution Universe survey - XI. Discovery of five recycled pulsars and the optical detectability of survey white dwarf companions - Bates, S.; Thornton, D.; Bailes, M.; Barr, E.; Bassa, C.; Bhat, Ramesh; Burgay, M.; Burke-Spolaor, S.; Champion, D.; Flynn, C.; Jameson, A.; Johnston, S.; et al. (Oxford University Press, 2015)
We present the discovery of a further five recycled pulsar systems in the mid-Galactic latitude portion of the High Time Resolution Universe survey. The pulsars have rotational periods ranging from 2 to 66 ms, and four are in binary systems with orbital periods between 10.8 h and 9 d. Three of these binary systems are particularly interesting; PSR J1227-6208 has a pulse period of 34.5 ms and the highest mass function of all pulsars with near-circular orbits. The circular orbit suggests that the companion is not another neutron star, so future timing experiments may reveal one of the heaviest white dwarfs ever found (>1.3 M☉). Timing observations of PSR J1431-4715 indicate that it is eclipsed by its companion which has a mass indicating it belongs to the redback class of eclipsing millisecond pulsars. PSR J1653-2054 has a companion with a minimum mass of only 0.08M☉, placing it among the class of pulsars with low-mass companions. Unlike the majority of such systems, however, no evidence of eclipses is seen at 1.4 GHz.